Fatigue life improvement using low transformation temperature weld material with measurement of residual stress. (November 2022) - Franks, Jordan; Wheatley, Greg; Zamani, Pedram; Masoudi Nejad, Reza; Macek, Wojciech; Branco, Ricardo; Samadi, Farzaneh
Highlights: This paper aims at addressing the effect of the LTT filler on residual stress fields and fatigue lifetime. The residual stress within each weld was quantified using the milling/strain gauge method. The fatigue tests were conducted under uniaxial loading. The results show that the crack propagation of all samples was similar in cycles although both LTT materials. It was found that both LTT materials reduced the residual tensile stresses. Abstract: Welding processes often produce high levels of tensile residual stress. Low transformation temperature (LTT) welding wires utilise phase transformation strains to overcome the thermal contraction of a cooling weld. In this paper, the residual stress within each weld was quantified using the milling/strain gauge method, being the strain change measured as the weldment was milled away. The fatigue tests were conducted under uniaxial loading considering two types of LTT materials. The results show that the crack propagation of all samples was similar in cycles although both LTT materials extended the crack initiation, and, therefore, the overall life of the part. It was found that both LTT materials reduced the residual tensile stresses, increased the residual compressive stresses, leading to increase in fatigue life about 30%.